Komunikasi Politik Era Modern - Winda Kustiawan; Najiah Maisaro Br Nst; Rayan Al-Ghazali (Universitas Muhammadiyah Enrekang, 2022)
Political communication is often heard in our ears, especially for the public and those who act as political figures. Political communication is not something new to hear and see. Political communication, which is commonly known as political advertising, is one that contains political messages and people involved in politics. Besides that, political communication messages are also closely tied to power, government and policies made by the government directly. Where political communication is usually an order for the governed. The modern era is an era where humans have ways of thinking from traditional to modern as well as in terms of Political Communication, humans have their own ways and views on Political Communication related to the development of the times from time to time to the current Modern era. In addition to science technology, especially Political Communication is also very developed in this era.